Palestine Blues - Sinnokrot, Nida (Dul'ab Films ; Radioaktive Films, 2005)
Verzio FF submission "Palestine Blues follows the repercussions of the Israeli Security Wall and Settlement expansion in the engulfed/annexed Palestinian farming communities of the West Bank and the Gaza Strip. Instead of focusing on the Wall as an object, Palestine Blues examines the grassroots resistance movement that has sprung up against it. Palestine Blues is not a 'traditional' political reportage but rather an interminable road trip across hard and liquid borders, across a terrain that is being erased as it is being traversed." - N. Sinnokrot